Water, Soil and Sediment Monitoring Programs; Some Lessons from 15 Years Experience in the Alligator Rivers Region, Northern Territory, Australia - McGill R. A; Noller B. N (The Australasian Institute of Mining and Metallurgy, 1994)
The Alligator Rivers Region has been the scene of one of Australia's most intensive environmental monitoring efforts since the current generation of uranium mining was mooted in the 1970s. Prior to mining, the local environment and the nature of potential impacts were not well known. The initial monitoring programs therefore included large baseline characterisation and research components. After some 15 years, water, soil and sediment monitoring programs have been reduced to a fraction of their early size, as the mining and natural systems became better known and characterised, and the actual nature of the environmental impacts were established. Modem techniques allow much more rapid and thorough identification of chemical species and elements of concern, allowing much more focused monitoring programs to be designed. In the 1980s data collection was emphasised at the expense of interpretation, and monitoring programs were maintained at much higher levels than were in fact required. It is now clear that investigations are important and should be distinguished from monitoring programs, and that the timely interpretation of investigations and implementation of recommendations can greatly reduce the effort and expense that can be involved in a monitoring program. Monitoring programs based on a sound understanding of potential environmental impact may then be efficient and cost-effective, yet provide sufficient information to assess the environmental impact of mining, guide further environmental protection measures when problems are detected, and demonstrate compliance with regulatory requirements.